Digital Islamic Counseling in the Digital Media Age: A Critical Review and Conceptual Model for Family Resilience and Well-Being - Arif, Moch. Choirul; Thohir, Mohamad (Proceedings Of International Conference On Islamic Counseling Studies (ICONICS), 2025)
Digital Islamic counseling is emerging as a key response to how social media and digital religion reshape family life in Muslim societies. This article develops a conceptual model of Digital Islamic Counseling for Family Resilience and Sustainable Well Being. A critical literature review synthesises sixty six peer reviewed studies from 2019 to 2024 on digital religion, Islamic counseling, family resilience, and sustainable well being. The analysis applies systematic search, screening, and thematic synthesis and organises the evidence into three main components.Results show that Muslim families inhabit dense digital faith and media ecosystems where online preachers, influencer da‘wa, and algorithmic curation expand access to Islamic learning while also intensifying commodification, polarisation, and misinformation. Islamic counseling grounded in Qur’anic principles, moral character, consultation, and spiritual coping can turn these environments into opportunities for shared meaning making, stronger parent child communication, and adaptive parenting when delivered through online counseling. The conceptual model links digital faith practices, counseling processes, and outcomes in family resilience and sustainable well being, and offers pathways for intervention.The study concludes that Digital Islamic Counseling provides a promising, faith informed framework for strengthening Muslim family resilience and sustainable well being and sets an agenda for future research and training.